FORMATION OF THE RESOURCE STRATEGY OF NAIL MANUFACTURING ENTERPRISES IN THE CONDITIONS OF MILITARY AGGRESSION - LUKIANOVA, Valentyna; KYRYLYUK, Maksym (Herald of Khmelnytskyi National University. Economic sciences, 2023)
This article is devoted to highlighting issues of resource strategy formation of industrial enterprises in conditions of military aggression. Attention is focused on the negative synergistic influence of external environmental factors on individual enterprises as participants in the production chain. The final product is defined as the production of nails. The main factors that negatively affected the metallurgical industry and other related sectors of the economy are presented. A retrospective analysis of individual sectors of the economy by main industrial groups was carried out in 2018-2022 and for 9 months of 2023. The results of the study are presented in the appropriate table and diagrams. The basic principles of developing a resource strategy of enterprises under the conditions of military aggression were formed: flexibility and additivity, realism, measurability, logic, alternativeness, complexity. The importance of following the general algorithm for the formation and implementation of the resource strategy of enterprises in the conditions of martial law in Ukraine and the implementation of its individual stages is emphasized. Four conditions have been identified that should ensure the effective functioning of enterprises in the conditions of martial law, as well as its resource strategy: ensuring the safety of personnel; ensuring the integrity and intactness of the company's material resources; formation of additional reserve stocks of raw materials and materials; search for alternative options for repurposing the enterprise. A number of additional measures are proposed to increase stability, competitiveness and ensure the sustainable development of the enterprise, namely: participation in enterprise associations; search for alternative (reserve) suppliers of materials; implementation of a system of continuous improvement of production processes and management practices; search for new sales markets; participation in state support programs for enterprises.
Keywords: resource strategy of enterprises; military aggression; nail production; main industrial groups; algorithm of formation and implementation of resource strategy of enterprises